Sustainable batik dyeing with ketapang (terminalia catappa) leaves: a practice-led experimental study on color retention and design innovation - Murwanti, Aprina; Hazmi, Fariz Al; Kamal, Fauzy Prasetya (International Journal of Visual and Performing Arts, 2025)
This study investigates the batik production process through a focused experimental approach on three key aspects: motif exploration, technique application, and the use of natural dyes extracted from Ketapang leaves. Employing a practice-led research methodology, the experiments were conducted at Rumoh Batik Malaka in Aceh Besar Regency, Aceh Province, Indonesia. Data were collected via systematic observation, experimental trials, and a comprehensive literature review. The color quality of batik samples was quantitatively assessed through RGB value analysis using grayscale imaging processed in MATLAB software. Results revealed that natural dyes derived from Ketapang leaves exhibit a measurable decline in color intensity when applied to batik textiles. Specifically, samples fixed with alum and calcium oxide and subjected to two dipping cycles showed significant fading, with grayscale values increasing from 0.5 to 0.7 post-wax removal (lorod). Conversely, optimal color retention was observed in samples fixed with ferrous sulfate and subjected to four dipping cycles, presenting minimal fading with values rising only from 0.1 to 0.2 after lorod. Six distinct batik pieces were produced, showcasing diverse motifs and color variations derived from the natural dye. The findings confirm that dye concentration and fixation type critically influence the colorfastness and aesthetic outcome, supporting the viability of Ketapang leaf extracts as sustainable natural dyes for cotton batik production. This research contributes to enriching batik design practices by promoting natural dye applications and innovative stamping techniques, offering ecological and cultural value to the textile arts in Indonesia and beyond.